2017
DOI: 10.1002/ecs2.2011
|View full text |Cite
|
Sign up to set email alerts
|

Climate of seed source affects susceptibility of coastal Douglas‐fir to foliage diseases

Abstract: Abstract. Seed-source movement trials using common garden experiments are needed to understand climate, tree (host), and pathogen interactions. Douglas-fir (Pseudotsuga menziesii var menziesii) is an important tree species native to western North America influenced by the foliar fungi Phaeocryptopus gaeumannii, a biotroph and causal agent of Swiss needle cast (SNC), and Rhabdocline species, necrotrophs that cause Rhabdocline needle cast. We used the Douglas-fir Seed-Source Movement Trial, a large provenance st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 64 publications
(193 reference statements)
0
19
0
Order By: Relevance
“…Thus defoliation should be analysed from a genetic perspective. Also, cultural control efforts could produce a ‘seed source’ inside the study area to increase needle tolerance to SNC (Wilhelmi et al., 2017) that reduces defoliation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus defoliation should be analysed from a genetic perspective. Also, cultural control efforts could produce a ‘seed source’ inside the study area to increase needle tolerance to SNC (Wilhelmi et al., 2017) that reduces defoliation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of genetic differentiation in coastal Douglas-fir found very low F ST values ranging between 0.006 and 0.071 [14, 37, 38]. Additionally, Wilhelmi et al [39] found differences in needle retention between provenances and concluded that provenances originating from areas of higher foliar disease pressure are more resistant. It can be therefore assumed that these traits are contributing to local adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…In western Oregon, winter temperature influences disease severity at a range of spatial and temporal scales (Manter et al, 2005;Stone et al, 2008a,b;Zhao et al, 2012;Lee et al, 2013Lee et al, , 2017Wilhelmi et al, 2017). Leaf canopy temperature may be a key predictor of variations in N. gaeumannii density within the canopy of mature Douglas-fir.…”
Section: Patterns Within Mature Tree Crownsmentioning
confidence: 99%